MANAJEMEN PERAN GANDA PEREMPUAN: STUDI KASUS IBU RUMAH TANGGA YANG BERPROFESI SEBAGAI GURU SD DAN MENEMPUH PENDIDIKAN TINGGI SETARA SATU (S-1) - Malida Malida; Nor Khafifah; Ahmad Salabi; Syaumi Safitri (Jurnal Manajemen Pendidikan, 2026)
This study aims to analyze the management of dual roles among women who work as elementary school teachers while simultaneously pursuing a bachelor's degree (S-1) and fulfilling their responsibilities as housewives in rural areas far from urban centers. The study employed a qualitative approach with a case study design. The research subjects were three housewives working as active elementary school teachers and currently enrolled in S-1 programs in rural settings. Data were collected through in-depth interviews, observation, and documentation. Data analysis followed the Miles, Huberman, and Saldana model, encompassing three stages: data reduction, data display, and conclusion drawing. The findings indicate that the subjects managed three primary roles concurrently through strict time management strategies, support from their immediate family particularly husbands and parents and strong intrinsic motivation grounded in improving the quality of student learning and self-actualization. These findings carry important implications for higher education institutions and the government to design flexibility-based education programs that are more responsive to the needs of rural women who bear dual roles.